Executive education as a tool for workforce capacity development: Evidence from Malaysian private sector employees - Fakhrorazi, A; Hartini, H; Omar, Rusdi; Ikhsan, Ridho Bramulya (Central Community Development Journal, 2025)
In the context of rapid economic change and increasing skill mismatches in Malaysia, understanding how private sector employees pursue continuing professional development has become a critical workforce development concern. This study explores the key factors motivating private-sector employees in Malaysia to enroll in executive academic programs, the benefits they expect, the skills most demanded by industry, and the learning structures and communication approaches that shape participation decisions. Data were collected using a drop-and-collect method and mail surveys, resulting in a final sample of 210 private sector employees. The findings indicate that career advancement, skill development, and networking opportunities are the primary drivers of participation. Leadership, critical thinking, problem-solving, and technical competencies such as financial management and data analysis emerge as the most sought-after skills. Respondents show a strong preference for hybrid learning formats and shorter program durations, alongside digitally mediated and personalized information channels when considering program enrollment. The findings provide practical insights for higher education providers, employers, and policymakers in designing development-oriented learning pathways that support private sector workforce capacity building and sustainable career progression.